Huellas del relato policial en México - Rodríguez Lozano, Miguel G. (Anales de Literatura Hispanoamericana, 2008)
The detective story in Mexico has a long and remarkable tradition to consider in works such as Rafael Bernal’s El complot mongol, Paco Ignacio Taibo II’s No habrá final feliz, or Bernardo Fernández’ Tiempo de alacranes. Nevertheless, the different hues and different ways to show this literary genre in the last century’s 90’s are relevant and still current until our days. The number of works and the heterogeneity of the narrative experience prove the authors’ attraction to subvert a tremendous flattened reality.